Studying the effect of seaweed extract on some growth characteristics of mung beans grown hydroponically (Eurasian Journal of Research, Development and Innovation, 2024)
The article is devoted to the role of operational-investigative activities in the customs authorities in identifying and suppressing crimes in the field of customs activities, as well as issues of the effective waysof its organization.